Sedekah Desa 'Karo Gedok': Sebuah Transformasi Budaya Masyarakat Tengger Lumajang 2010: Village Alms 'Karo Gedok': A Cultural Transformation of the Tengger Lumajang Community in 2010 - Rusydi Baya’gub (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
Village alms is one of the cultural rituals performed by the Tengger tribe community. In addition, there are traditional ceremonies such as Karo, Kasada, Entas-entas, and Unan-unan. The village alms conducted by the residents of Gedok Hamlet, Argosari Village, Senduro District, Lumajang Regency, is a duplication or transformation of the local Hindu Karo ritual. This ritual is carried out every second day of Eid al-Fitr or Eid al-Adha. Its purpose is as a manifestation of gratitude to God Almighty and a petition for the safety of the residents and their homes from all disasters. Sedekah desa adalah salah satu ritual budaya yang dilakukan oleh masyarakat Suku Tengger. Selain itu, terdapat juga upacara adat Karo, Kasada, Entas-entas, dan Unan-unan. Sedekah desa yang dilakukan oleh warga Dusun Gedok, Desa Argosari, Kecamatan Senduro, Kabupaten Lumajang, merupakan duplikasi atau transformasi dari ritual Karo dalam agama Hindu lokal. Ritual ini dilaksanakan setiap hari kedua pada hari raya Idul Fitri atau Idul Adha. Tujuan dan tujuannya adalah sebagai wujud rasa syukur kepada Tuhan Yang Maha Esa serta permohonan keselamatan warga dan tempat tinggal mereka dari segala musibah.